Chemical kinetics of near-surface ozone at a suburban location in India - Sagar, Vijay Kumar; Kanchana, Asuri Lakshmi; Nayak, Rabindra Kumar; Fadnavis, Suvarna; Kanawade, Vijay P. (Frontiers in Environmental Science, 2023)
The spatial gradient in near-surface ozone (O3) is controlled by its production, sink, and net transport (advective/convection and diffusive) in the atmosphere. In this work, we used continuous long-term measurements of O3, oxides of nitrogen (NOx=NO+NO2), and meteorological data in the suburban location of Shadnagar, India. Data analyses were performed to investigate the governing processes that control the O3 variability on diurnal and seasonal time scales. The role of chemistry in the O3 variability, including both formation and destruction processes, has been investigated using known chemical kinetics and radiative transfer model. The residual between observations and chemical estimation was further analyzed to examine the role of transport and unresolved processes/uncertainty in the dataset. The O3 residual was duly validated using model reanalysis data of O3 and meteorological parameters to further estimate the O3 transport. Our analyses show that the average net production and net transport of near-surface O3 are 3.18 ppbv/hour and 0.87 ppbv/hour, respectively, while horizontal advection is 0.01 ppbv/h in the daytime. The production of ozone was found to be dominant indicating the influx of ozone at the site. Overall, our results highlight that spatio-temporal variability in near-surface ozone is strongly controlled by net production in Shadnagar and may be applicable in similar environments globally.